The effect of a mental training program in swimmer's anxiety levels - Zientek, C. (Biomechanics and Medicine in Swimming IX, 2003)
INTRODUCTION The effect of competitive anxiety on sport performance has been researched in an effort to examine and control the negative effects of anxiety on sport performance. Instruments were developed to measure competitive anxiety, including the Competitive State Anxiety Inventory-2 (CSAI-2) that measures cognitive anxiety, somatic anxiety, and selfconfidence (Martens, et al. 1990). Results of previous studies have shown a negative linear relationship between cognitive anxiety and performance, a curvilinear relationship between somatic anxiety and performance, and a positive linear relationship between self-confidence and performance. The purpose of the present study was to assess the impact of an eight-week mental training program on competitive state anxiety levels of swimmers. METHODS Prior to and after the intervention, university level swimmers (N=50) completed the CSAI-2 that measured cognitive anxiety, somatic anxiety, and self-confidence (Martens et. al., 1990). The intervention program consisted of three phases: 1) relaxation/arousal control and imagery, 2) individual goal setting, and 3) strategy planning (Hogg, 2000). RESULTS Paired sample t-tests revealed significant decreases in cognitive anxiety (t = -4.27, p<.01) following the intervention, with mean scores being reduced from 22.00 to 18.94. Somatic anxiety scores were reduced from 20.04 to 15.47 (t = -7.76, p<.01). Self-confidence levels were high and remained unchanged. Multivariate analysis revealed significant gender differences. Prior to the intervention, females were more cognitively anxious [F (1,49) =4.42, p<.05] and less confident [F (1,49) =7.65, p<.01] than males, although no gender differences were found in cognitive anxiety. After intervention, no significant gender differences existed with regard to cognitive anxiety, somatic anxiety, or self-confidence. DISCUSSION Norms for both cognitive and somatic anxiety have been studied by Martens et al. (1990), and were 16.5 for both types of anxiety in previous studies. Swimmers in the present study were extremely high in both cognitive and somatic anxiety pre-intervention. The present study serves to demonstrate that cognitive and somatic anxiety scores can be controlled in an effort to eliminate the negative effects of high levels of anxiety.